Documenting disaster in Yogyakarta: A case study of earthquake on May 27 th, 2006 - Bramantya, Arif Rahman; Sugiharto; Lillyana Mulya (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: The documenting of disasters through oral history programs carried out by educational institutions, archival institutions, memory institutions, and archival activists in the last few decades has begun to develop. The factors that have strongly led to the emergence of this phenomenon refer to the awareness of the importance of preserving information and historical awareness related to the shaping of memory. Purpose: This study analyzes the contribution of oral history archives in forming social memory related to the Yogyakarta earthquake on May 27th, 2006, in a more communicative and creative dimension. Method: This research is qualitative research conducted through interviews, observations, and literature studies Findings: The Yogyakarta earthquake on May 27, 2006, has been placed in social memory through oral history archives and media reports that are remembered in social reality. Oral history archives are also presented creatively and collaboratively as a form of public history through Archival Dioramas at the Dinas Perpustakaan dan Arsip Daerah Daerah Istimewa Yogyakarta. The results of victims' experiences in oral history re-interviews can be analyzed in the context of the resilience of social memory. Conclusion: The emergence of digital equipment impacts people's interest, awareness, and motivation to engage in disaster documentation, shaping social memory in Yogyakarta.